Optimal Combination of Anodal Transcranial Direct Current Stimulations and Motor Imagery Interventions. (2nd April 2018) - Saruco, Elodie; Di Rienzo, Franck; Nunez-Nagy, Susana; Rubio-Gonzalez, Miguel A.; Debarnot, Ursula; Collet, Christian; Guillot, Aymeric; Saimpont, Arnaud
Abstract : Motor imagery contributes to enhance the (re)learning of motor skills through remapping of cortical networks. Combining motor imagery with anodal transcranial direct-current stimulation (a-tDCS) over the primary motor cortex has further been shown to promote its beneficial effects on postural control. Whether motor imagery should be performed concomitantly to a-tDCS (over depolarized membrane) or consecutively (over changing neurotransmitters activity) remains to be elucidated. In the present study, we measured the performance in a postural control task before and after three experimental conditions. Participants received a-tDCS before (tDCSBefore ), during (tDCSDuring ), or both before and during motor imagery training (tDCSBefore + During ). Performance was improved after tDCSDuring, but not after both the tDCSBefore and tDCSBefore + During conditions. These results support that homeostatic plasticity is likely to operate following a-tDCS through decreasing cortical excitability and that motor imagery should be performed during anodal stimulation for optimum gains.